Influence of upright versus time trial cycling position on determination of critical power and W' in trained cyclists - Kordi, M.; Fullerton, C.; Passfield, L.; Parker Simpson, L. (European Journal of Sport Science, 2019)
Body position is known to alter power production and affect cycling performance. The aim of this study was to compare mechanical power output in two riding positions, and to calculate the effects on critical power (CP) and W' estimates. Seven trained cyclists completed three peak power output efforts and three fixed-duration trial (3-, 5- and 12-min) riding with their hands on the brake lever hoods (BLH), or in a time trial position (TTP). A repeated-measures analysis of variance showed that mean power output during the 5-min trial was significantly different between BLH and TTP positions, resulting in a significantly lower estimate of CP, but not W', for the TTP trial. In addition, TTP decreased the performance during each trial and increased the percentage difference between BLH and TTP with greater trial duration. There were no differences in pedal cadence or heart rate during the 3-min trial; however, TTP results for the 12-min trial showed a significant fall in pedal cadence and a significant rise in heart rate. The findings suggest that cycling position affects power output and influences consequent CP values. Therefore, cyclists and coaches should consider the cycling position used when calculating CP.